2007
DOI: 10.1136/emj.2007.048207
|View full text |Cite
|
Sign up to set email alerts
|

TIMI risk score: does it work equally well in both males and females?

Abstract: The TIMI risk score successfully risk stratifies both males and females with potential ACS at the time of ED presentation; however, males have worse outcomes at lower TIMI scores than females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…Third, the role of proportion of males recruited in the trials was, in our meta‐regression, ambiguous—higher proportion of males was beneficial for the outcome of MBG < 3, detrimental for the outcome of a failed STR, and neutral for the outcome of TIMI < 3. While there appears to be no direct biological explanation for this observation, our observation points toward an important area that future studies in outcomes research need to explore, especially since mortality rates associated with PCI have been reported in various studies to be influenced by gender 51–56 . Fourth, the meta‐regression identified that the time of assessment of STR may be an important predictor of the trial heterogeneity—a finding that corroborates the observation that it is more useful to assess STR at 60 minutes rather than 90 minutes 57 .…”
Section: Discussionsupporting
confidence: 73%
“…Third, the role of proportion of males recruited in the trials was, in our meta‐regression, ambiguous—higher proportion of males was beneficial for the outcome of MBG < 3, detrimental for the outcome of a failed STR, and neutral for the outcome of TIMI < 3. While there appears to be no direct biological explanation for this observation, our observation points toward an important area that future studies in outcomes research need to explore, especially since mortality rates associated with PCI have been reported in various studies to be influenced by gender 51–56 . Fourth, the meta‐regression identified that the time of assessment of STR may be an important predictor of the trial heterogeneity—a finding that corroborates the observation that it is more useful to assess STR at 60 minutes rather than 90 minutes 57 .…”
Section: Discussionsupporting
confidence: 73%
“…These patients may then be more likely to undergo coronary revascularisation procedures as a result. Nonetheless, previous similar research has utilised the same composite outcome 13 15 16 18 2426. Despite the potential sources of bias the composite outcome is currently the most practical, reliable and objective measure of short-term outcome that we have for this population.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients presenting to the emergency department with chest pain, the TIMI risk score performed well in both men and women for the prediction of death or MI at 30 days. 412 In another recent study, prognostic indicators such as left ventricular ejection fraction and ECG parameters (heart rate, heart rate variability, non-sinus rhythm, and QRS width) predicted 5-year mortality in both women and men, but there were some differences in magnitude of effects between women and men. For example, the absence of sinus rhythm was associated with a hazard ratio of 7.6 in women and 3.2 in men.…”
Section: Markers Of Disease Severitymentioning
confidence: 97%